Sikap Orang Madura dalam Novel Ojung Karya Edi Ah Iyubenu - Muhammad Tauhed Supratman; Rahmad Rahmad (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Characters and attitudes are often raised in a story or literary work involving the author himself to bring out what he has experienced, so that the reader can be clearly known by humanity's attitude as described in Ojung's novel. The novel, describes the attitude of Madurese people who are diverse in dealing with social problems such as brave attitude to bear the risks possessed by the main sitokoh, a very high attitude of confidence and confidence will come something he believes, egoism and ambition, willingness to sacrifice and virtuous tall one. Attitudes in a literary work can be diverse, including brave attitudes, high manners, selfishness, jealousy and envy of all and so on. The method used is a qualitative method. The results of the study illustrate the attitude of the Madurese people such as: the attitude of upholding self-esteem, courageous attitude to bear the risk.